Echocardiographic partition values and prevalence of left ventricular hypertrophy in hypertensive Nigerians - Oladapo Olulola O (BMC Medical Imaging, 2006)
Abstract Background Left ventricular hypertrophy (LVH) is a well known independent risk factor for cardiovascular events. It has been shown that combination of left ventricular mass (LVM) and relative wall thickness (RWT) can be used to identify different forms of left ventricular (LV) geometry. Prospective studies have shown that LV geometric patterns have prognostic implications, with the worst prognosis associated with concentric hypertrophy. The methods for the normalization or indexation of LVM have also recently been shown to confer some prognostic value especially in obese population. We sought to determine the prevalence of echocardiographic lLVH using eight different and published cut-off or threshold values in hypertensive subjects seen in a developing country's tertiary centre. Methods Echocardiography was performed in four hundred and eighty consecutive hypertensive subjects attending the cardiology clinic of the University college Hospital Ibadan, Nigeria over a two-year period. Results Complete data was obtained in 457 (95.2%) of the 480 subjects (48.6% women). The prevalence of LVH ranged between 30.9–56.0%. The highest prevalence was when LVM was indexed to the power of 2.7 with a partition value of 49.2 g/ht2.7 in men and 46.7 g/ht2.7 in women. The lowest prevalence was observed when LVM was indexed to body surface area (BSA) and a partition value of 125 g/m2 was used for both sexes. Abnormal LV geometry was present in 61.1%–74.0% of our subjects and commoner in women. Conclusion The prevalence of LVH hypertensive patients is strongly dependent on the cut-off value used to define it. Large-scale prospective study will be needed to determine the prognostic implications of the different LV geometry in native Africans.